The Underlying Motivational Process Behind Faculty Members’ Voice Behavior : An Experimental Design - Satpathy, Durgesh; Jeswani, Saket; Dubey, Archi (Prabandhan: Indian Journal of Management, 2024)
Purpose : The objective of this study was to examine the influence of employee value propositions (EVP) on psychological contract (PC), assess the mediating role of PC between EVP and employee voice behavior (EVB), examine the moderating effect of motivational orientation on the relationship between PC and employee voices, and evaluate the impact of situational stimuli on employee voices. Methodology : A quasi-experimental study was conducted to analyze the relationship between variables. In the pre-post intervention, 242 faculty members from three premier higher educational institutes in India participated. Structural equation modeling was used through SmartPLS 3.0 software for data analysis. Findings : The findings confirmed that PC influences the association between faculty members’ voice conduct and EVP. Additionally, the research demonstrated a favorable and significant moderating influence of promotion focus between PC and promotive voice. However, when situational stimuli are present, this relationship becomes unfavorable. In a similar vein, prevention-focused had a favorable and significant moderating effect between PC and preventative voice, but it turned negative in response to situational cues. Practical Implications : In view of the study’s conclusions on the influence of situational stimuli on EVB, management ought to evaluate staff members’ opinions of PC fulfillment and EVP. This knowledge made it possible to implement customized actions to resolve differences in employee opinions, successfully coordinating situational factors with corporate objectives. Originality : This study added a new angle to PC research by utilizing the regulatory focus theory (RFT). Motivational orientation was found to be a strong moderator between PC and EVB, which is unique to this study. The study made a unique contribution to the area by demonstrating how voice behavior changes in response to situational inputs.